2017
DOI: 10.1094/mpmi-06-17-0151-r
|View full text |Cite
|
Sign up to set email alerts
|

Recombination of Virulence Genes in Divergent Acidovorax avenae Strains That Infect a Common Host

Abstract: Bacterial etiolation and decline (BED), caused by Acidovorax avenae, is an emerging disease of creeping bentgrass on golf courses in the United States. We performed the first comprehensive analysis of A. avenae on a nationwide collection of turfgrass- and maize-pathogenic A. avenae. Surprisingly, our results reveal that the turfgrass-pathogenic A. avenae in North America are not only highly divergent but also belong to two distinct phylogroups. Both phylogroups specifically infect turfgrass but are more closel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…We believe that the genetic diversity calculated from this study is a better representation of the true scenario of the SI E. amylovora strains. Despite this, the overall diversity of SI E. amylovora strains was still very low in comparison with other pathogens that have emerged in recent years (McCann et al ., ; Potnis et al ., ; Zeng et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…We believe that the genetic diversity calculated from this study is a better representation of the true scenario of the SI E. amylovora strains. Despite this, the overall diversity of SI E. amylovora strains was still very low in comparison with other pathogens that have emerged in recent years (McCann et al ., ; Potnis et al ., ; Zeng et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The overall diversity of the 30 SI E. amylovora genomes, as determined by Watterson's theta (Watterson, 1975), was 8.18 310 24 per site, which is at least 100-fold lower than that of other bacterial plant pathogens, such as the kiwifruit pathogen Pseudomonas syringae pv. actinidiae and the turfgrass pathogen Acidovorax avenae (Watterson's theta values determined as 0.008 and 0.0279, respectively) (McCann et al, 2013;Zeng et al, 2017). However, when compared with a previous comparative genomics study of E. amylovora, the genetic diversity of E. amylovora determined by our study was approximately 33 times higher (nucleotide pairwise identity was 99.90% in this study, compared with the amino acid pairwise identity of 99.98% of coding regions, or nucleotide pairwise identity of 99.997% on the whole genome, in the previous study).…”
Section: Collection Of Fire Blight Samples and Isolation Of E Amylovmentioning
confidence: 99%
See 2 more Smart Citations
“…A phylogenetic analysis confirmed that the recombinant hrp/hrc genes shared a common evolutionary history with that of phylogroup 2a (Figure 4) and therefore, may be a significant factor contributing to the convergent pathogenicity of 2a and 2b-a lineages to cucurbit hosts. This finding was reminiscent of bacterial etiolation and decline of creeping bentgrass, for which the host-specificity of two phylogenetically distinct Acidovorax avenae populations was associated with three ancestral recombination events affecting the hrp/hrc gene cluster (Zeng et al, 2017).…”
Section: Discussionmentioning
confidence: 98%